Type of syncope and outcome in Brugada syndrome: A systematic review and meta‐analysis - Pattara Rattanawong; Jakrin Kewcharoen; Thanaboon Yinadsawaphan; Olubadewa A. Fatunde; Chanavuth Kanitsoraphan; Wasawat Vutthikraivit; Narut Prasitlumkum; Eugene H. Chung; Win‐Kuang Shen (Journal of Arrhythmia, 2023)
Abstract Introduction Brugada syndrome is an inherited arrhythmic disease associated with major arrhythmic events (MAE). The importance of primary prevention of sudden cardiac death (SCD) in Brugada syndrome is well recognized; however, ventricular arrhythmia risk stratification remains challenging and controversial. We aimed to assess the association of type of syncope with MAE via systematic review and meta‐analysis. Methods We comprehensively searched the databases of MEDLINE and EMBASE from inception to December 2021. Included studies were cohort (prospective or retrospective) studies that reported the types of syncope (cardiac, unexplained, vasovagal, and undifferentiated) and MAE. Data from each study were combined using the random‐effects, generic inverse variance method of DerSimonian and Laird to calculate the odds ratio (OR) and 95% confidence intervals (CIs). Results Seventeen studies from 2005 to 2019 were included in this meta‐analysis involving 4355 Brugada syndrome patients. Overall, syncope was significantly associated with an increased risk of MAE in Brugada syndrome (OR = 3.90, 95% CI: 2.22–6.85, p < .001, I2 = 76.0%). By syncope type, cardiac (OR = 4.48, 95% CI: 2.87–7.01, p < .001, I2 = 0.0%) and unexplained (OR = 4.71, 95% CI: 1.34–16.57, p = .016, I2 = 37.3%) syncope was significantly associated with increased risk of MAE in Brugada syndrome. Vasovagal (OR = 2.90, 95% CI: 0.09–98.45, p = .554, I2 = 70.9%) and undifferentiated syncope (OR = 2.01, 95% CI: 1.00–4.03, p = .050, I2 = 64.6%, respectively) were not. Conclusion Our study demonstrated that cardiac and unexplained syncope was associated with MAE risk in Brugada syndrome populations but not in vasovagal syncope and undifferentiated syncope. Unexplained syncope is associated with a similar increased risk of MAE compared to cardiac syncope.